FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPESERTAAN SEKTOR INFORMAL DALAM BPJS KESEHATAN MANDIRI DI KELURAHAN PONCOL, KECAMATAN PEKALONGAN TIMUR, KOTA PEKALONGAN - Viona Febya Pangestika; Sutopo Patria Jati; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2017)
To realize Universal Health Coverage 2019, being a National Health Insurance participant is not only mandatory for the formal sector only. But the informal sector is also required to follow the National Health Insurance. In Kota Pekalongan, the majority of the population work in the informal sector (self-employed or merchant), but for the achievement of the National Health Insurance participation in the self-employed workers is 14.39%. The purpose of this study is to identify and analyze factors related to informal sector participation in BPJS Self Health. Quantitative research type with analytical method, cross sectional approach, and using Chi Square test. The sample size is 106 respondents who are self-employed main livelihoods / traders. The results showed that most of the respondents were badly knowledgeable (50.9%), the number of family dependents 2-4 people (88.7%), income above UMR (96.2%), monthly average expenditure less than income (90.6%), paying premiums (55.0%), having the ability to pay premiums (61.3%), and low family support (70.8%). Variables related to informal sector participation in BPJS Self health is average monthly expenditure (p = 0.001), willingness to pay (p = 0.000), ability to pay (p = 0.000), and family support (p = 0.009). While unrelated variables were knowledge (p = 0.053), total family dependent (p = 0.635), and income (p = 0.050). Economic situation and family support become the main factor of participation of informal sector in BPJS Self Health. The community, especially the informal sector, is expected to participate actively and implement the information about BPJS Health that has been received by setting aside some of its income to become a participant of BPJS Self Health. For BPJS Health socialization to the layers of RT is very necessary through cooperation with the cadres Puskesmas.